UTILIZAREA TERENURILOR ÎN CULOARUL TÂRNAVEI MARI ÎNTRE BLAJ ŞI COPŞA MICĂ (PANGEEA, 2025)
Land use in Târnava Mare lane, between Blaj and Copşa Mică. Humans have continually reshaped the Earth, but the present magnitude and rate are unprecedented. Nowadays, it is realized that it is very important to know how land cover has changed over time, in order to make assessments of the changes one could expect in the (near) future and the impact these changes will have on peoples' lives. As people are the main users of the land, it is important for any system to be oriented towards them.